177Lu-dotatate use in chronic kidney disease patients: A single center experience. Issue 3 (October 2021) - Manohar, Sandhya; Kompotiatis, Panagiotis; Halfdanarson, Thorvardur R; Hobday, Timothy J; Thorpe, Matthew; Johnson, Geoffrey B; Kendi, Ayse Tuba; Leung, Nelson
Background: Peptide receptor radionuclide therapy with 177 Lu-dotatate is a novel therapy for metastatic neuroendocrine cancers. It undergoes reabsorption at the proximal tubule; after the breakdown of the peptide fragment, 177 Lu is retained and continues its decay process exposing the nephron to continuous low dose radiation. Pivotal NETTER-1 trial did not include patients with eGFR <50 and so its effects in CKD patients is not known. Methods: We performed a retrospective chart review of all consecutive adult patients that received 177 Lu-dotatate over 1 year at Mayo Clinic, Rochester. We analyzed renal and hematological laboratory data obtained prior to each of four treatment cycles and at 3- and 6-month post completion of all treatment. We defined CKD as eGFR <60 ml/min and AKI as creatinine increase of ⩾0.3 from baseline by AKIN criteria. Results: Overall 86 patients were included in the study with 39 (45%) with known CKD. About three patients had CKD, four with eGFR of 20–30 ml/min. About 4 (4.6%) patients had AKI and the predominant cause being hypotension. Among the CKD patients the average eGFR improved after the first cycle of PRRT therapy from baseline of 49 (13) to 53.5 (17) ml/min ( p  = 0.01) with no significant decline of renal function noted at 3- and 6-months post treatment follow up. Rate of thrombocytopenia and leukopenia were significantly more in the CKD patients starting even after single treatment. No drug dose correlation was noted. Conclusion: Patients with CKD are at a higher risk of hematological toxicity especially with thrombocytopenia and require close monitoring and ongoing dose adjustment. Ongoing safety studies to assess the long-term impact of 177 Lu-dotatate on the kidney are needed.